2013
DOI: 10.3109/10428194.2013.816423
|View full text |Cite
|
Sign up to set email alerts
|

Impaired B-cell reconstitution in children after chemotherapy for standard or medium risk acute precursor B-lymphoblastic leukemia

Abstract: Chemotherapy for childhood acute lymphoblastic leukemia (ALL) is a highly effective treatment, but at the same time causes significant suppression of the patient's immunity. Immune reconstitution was studied in a homogeneous cohort of 48 children with standard or medium risk ALL treated according to the ALL-Berlin-Frankfurt-Münster (BFM) protocol. Whereas the T-cell compartment was only moderately affected and recovered to normal levels quickly after treatment cessation, B-cells were significantly reduced duri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
36
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(38 citation statements)
references
References 27 publications
2
36
0
Order By: Relevance
“…Our results on the dynamics of B-cell subsets in BM and PB during and after ALL therapy showed that chemotherapy dramatically affected the BCP population in BM and the mature B-cell population in PB, which was in agreement with previous studies (van Lochem et al, 2000;van Wering et al, 2000;Eyrich et al, 2009;van Tilburg et al, 2011;Wiegering et al, 2014). The two therapy-intervals (with a duration of 1 and 2 weeks, respectively) were too short to achieve complete BCP differentiation in BM and therefore too short to replenish the PB with new mature B-cells.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Our results on the dynamics of B-cell subsets in BM and PB during and after ALL therapy showed that chemotherapy dramatically affected the BCP population in BM and the mature B-cell population in PB, which was in agreement with previous studies (van Lochem et al, 2000;van Wering et al, 2000;Eyrich et al, 2009;van Tilburg et al, 2011;Wiegering et al, 2014). The two therapy-intervals (with a duration of 1 and 2 weeks, respectively) were too short to achieve complete BCP differentiation in BM and therefore too short to replenish the PB with new mature B-cells.…”
Section: Discussionsupporting
confidence: 93%
“…The normal B-cell compartment can be severely affected in patients receiving chemotherapy regimens (Steele, 2002;Lehrnbecher et al, 2008). Profound B-lymphocytopenia as a result of chemotherapy was previously reported in patients with solid tumours treated with docetaxel, patients with breast cancer treated with anthracycline-based regimens and patients with acute lymphoblastic leukaemia (ALL) treated with multidrug chemotherapy (Kotsakis et al, 2000;van Lochem et al, 2000;van Wering et al, 2000;Eyrich et al, 2009;van Tilburg et al, 2011;Wiegering et al, 2014;Verma et al, 2016). In the latter patients, T-cells, particularly CD8 + T-cells, are significantly less affected by chemotherapy (Ek et al, 2005;Lehrnbecher et al, 2008;van Tilburg et al, 2011).…”
mentioning
confidence: 99%
“…B-lymphoblastic leukemia/lymphoma, also known as B-acute lymphoblastic leukemia (B-ALL), is a hematological malignancy that is derived from B cell progenitors. B-ALL occurs at any age but is predominantly seen in children [ 1 , 2 ]. Risk-adapted intensive chemotherapy is effective in treating most children with B-ALL, but this approach is less successful in adults [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…Our group reported on the influence of immune function under chemotherapy in standard‐risk (SR) ALL patients. We showed that during chemotherapy in SR and intermediate‐risk paediatric ALL patients, the T‐cell system remained relatively well preserved, whereas B‐cell depletion was observed .…”
Section: Introductionmentioning
confidence: 99%